The Effect of Work Stress on Turnover Intention Mediated by Employee Engagement and Job Satisfaction - Handayani, Susie; Berliyanti, Dita Oki; Nilasari, Medina (Jurnal Economic Resource, 2025)
This study was conducted to examine the effect of work stress on turnover intention, both directly and indirectly through employee engagement and employee satisfaction. The research design used was a causal study that aimed to examine the effect of independent variables on dependent variables using mediating variables. The research variables used consist of one independent variable, namely work stress, two mediating variables, namely employee engagement and job satisfaction, and one dependent variable, namely turnover intention. The sample used was employees working at public accounting firms in Jakarta. From the data collection conducted using Google Forms, a sample of 123 people was obtained. The analysis tool used was SEM-PLS, processed using Smart-PLS software. The results of the analysis revealed the following findings: 1) work stress was not proven to influence turnover intention; 2) work stress was not proven to influence employee engagement; 3) work stress was proven to have a significant negative influence on job satisfaction; 4) employee engagement was proven to have a significant negative influence on turnover intention; 5) job satisfaction was found to influence turnover intention; 6) employee engagement was not found to mediate the negative influence of work stress on turnover intention; and 7) work stress was found to have a positive influence on turnover intention.